Science–Religion Interaction: Exploring the Grounds, Delineating a Framework - Zargar, Zahra (Theology and science, 2024)
The early inquiries on the science-religion relationship have focused exclusively on their epistemic aspects for describing the essence of their relationship. However, the recent theories include practical and social aspects of science and religion, and seek models that support plurality, complexity, and dynamic aspects of them. In this paper, I follow two aims. First, I want to explore the implications of the recent theories for the existence of an inevitable dynamic and fruitful interaction between science and religion. Second, I try to delineate a framework for conducting science–religion interactive projects that preserves the authority of both systems, and prevents vicious and illegitimate results.